1983
DOI: 10.1901/jaba.1983.16-253
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Interventions and Driving Speed: A Parametric and Comparative Analysis

Abstract: Five experiments were conducted to assess the effects of several variables on the efficacy of feedback in reducing driving speed. Experiment 1 systematically varied the criterion used to define speeding, and results showed that the use of a lenient criterion (20 km/hr over the speed limit), which allowed for the posting of high percentages of drivers not speeding, was more effective in reducing speeding than the use of a stringent criterion (10 km/hr over the speed limit). In Experiment 2 an analysis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 4 publications
0
35
1
Order By: Relevance
“…Third, the use of warnings allowed police to contact up to 20 times as many noncompliant motorists. Data show that the use of warnings greatly increases the effectiveness of enforcement (Van Houten & Nau, 1983), and a high frequency of stops ensures not only that many people directly make contact with the punishment contingency but also that many drivers witness these stops. It is interesting to note that after a few taxi drivers were cited for failing to yield during the first couple of days of the program, taxi drivers began to yield reliably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the use of warnings allowed police to contact up to 20 times as many noncompliant motorists. Data show that the use of warnings greatly increases the effectiveness of enforcement (Van Houten & Nau, 1983), and a high frequency of stops ensures not only that many people directly make contact with the punishment contingency but also that many drivers witness these stops. It is interesting to note that after a few taxi drivers were cited for failing to yield during the first couple of days of the program, taxi drivers began to yield reliably.…”
Section: Discussionmentioning
confidence: 99%
“…One way to modify driver behavior is through enforcement programs. Van Houten and Nau (1983) compared the effects of an enforcement program that issued citations with one that issued primarily written and verbal warnings on speeding on urban streets. The results indicated that the effects of a 1-week enforcement program, which relied on citations alone, persisted only while the program was in effect, but that the effects of the warning program persisted for up to a year.…”
mentioning
confidence: 99%
“…Although few drivers directly experienced the aversive consequence of a fine, many more may have seen police cars patrolling handicapped parking sites and ticketing violators. Van Houten and Nau (1983) and Van Houten et al (1985) indicated that the effectiveness ofpolice enforcement procedures may be a function of the density and visibility of punishment.…”
Section: Social Validity Datamentioning
confidence: 99%
“…Issues have included littering (Geller, Winett, & Everett, 1982), trash packaging (Stokes & Fawcett, 1977), city crime (Schnelle, Kirchner, Casey, Uselton, & McNees, 1977), and speeding (Van Houten & Nau, 1983;Van Houten et al, 1985).…”
mentioning
confidence: 99%
“…Feedback has been shown to be effective in reducing the incidence of speeding (Van Houten & Nau, 1983) and to increase yielding to pedestrians (Van Houten, Malenfant, & Rolider, 1985). Geller and his associates have suggested that providing feedback on alcohol impairment might be similarly effective in reducing the incidence ofimpaired driving (Geller, Altomari, & Russ, 1984;Geller & Lehman, 1988; Russ, 1986).…”
mentioning
confidence: 99%